Hvornår oprettedes dominikanerklosteret i Haderslev? En genopdaget indskrift bekræfter en formodning om tidspunktet for prædikebrødrenes ankomst - Jakobsen, Johnny Grandjean Gøgsig (Kirkehistoriske Samlinger, 2010)
Summary In Danish monastic history writing, it has for long been an established fact that the Dominican Friars Preachers founded a convent in Haderslev around the middle of the thirteenth century. The first mentioning of such a convent is from the provincial chapter acts of the order itself in 1254, in which two friars are decided moved to Haderslev from the convent in Århus. Based on this, it is traditionally suggested in the literature that the Dominicans must have come to Haderslev in 1254 or rather in the preceding years, setting the period 1249-1253 as the most likely time span for the convent foundation. This period fits very well with the theory that the main reason for a Dominican foundation in Haderslev was the contemporary organisation of a small canonical chapter at the Church of St. Mary and an ecclesiastical school for the education of secular priests in the northern part of the diocese of Schleswig. It is, however, possible to pin-point the exact year of the Dominican foundation in Haderslev, at least according to one medieval source that monastic historians in Denmark apparently has neglected to notice until now, although published in 1913. In the choir stools of the Dominican church in the small north-German town of Röbel, located between Rostock and Berlin, a friar called Urban Schuman in 1519 made an inscription, naming 26 Dominican convents in the German province of Saxonia, putting a date on the year of their foundation. Among them we find the convent of Haderslev, which was transferred from the Scandinavian province of Dacia to Saxonia two years before, and according to Fr. Urban, the convent in Haderslev was established in 1251. Of course, this claim written in a Röbel choir stool does not have to be the final truth inthe matter, but the stated year does fit beautifully with all other facts and speculations around it, and since most of his priory datings seem to be correct, I see no reason why we should not take Fr. Urban’s word for it: The Dominican convent in Haderslev was probably founded in 1251.